A perfect life [compact disc, unabridged] : a novel - Steel, Danielle (Brilliance Audio, Inc., 2014)
Blaise is a famous anchor on morning news and a legend in her field. In order to rise to the top, she had to place her blind daughter, Salima, in a boarding school. When tragedy hits, Salima is forced to move in with Blaise. They both have to contend with a new caretaker who has little patience for indulging Salima's handicap. Blaise can't deny that Salima seems to be improving under Simon's supervision, while his movie star looks and attempts at real friendship become difficult to ignore.